Circadian rhythms and second language performance - de Bot, Kees; Fang, Fang (Studies in Second Language Learning and Teaching, 2017)
Human behavior is not constant over the hours of the day, and there are considerable individual differences. Some people raise early and go to bed early and have their peek performance early in the day (“larks”) while others tend to go to bed late and get up late and have their best performance later in the day (“owls”). In this contribution we report on three projects on the role of chronotype (CT) in language processing and learning. The first study (de Bot, 2013) reports on the impact of CT on language learning aptitude and word learning. The second project was reported in Fang (2015) and looks at CT and executive functions, in particular inhibition as measured by variants of the Stroop test. The third project aimed at assessing lexical access in L1 and L2 at preferred and non-preferred times of the day. The data suggest that there are effects of CT on language learning and processing. There is a small effect of CT on language aptitude and a stronger effect of CT on lexical access in the first and second language. The lack of significance for other tasks is mainly caused by the large interindividual and intraindividual variation.